AI Ethics and Health Equity: Does AI Respect Vulnerable Populations? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Does AI Respect Vulnerable Populations? An Ethical Imperative in Digital Health The rapid integration of Artificial Intelligence (AI) into healthcare an...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Precision Medicine